2019
DOI: 10.1029/2019jd030245
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Impact of the Autumn Tibetan Plateau Snow Cover on the Winter Temperature Over North America in the mid‐1990s

Abstract: This study investigates the changes in the impact of the interannual variation of autumn snow cover over the eastern Tibetan Plateau (TP; ASCETP) on winter surface air temperature (SAT) over North America (NA) in the mid‐1990s using both observational data and a linear baroclinic numerical model. The index of ASCETP shows an abrupt change with a predominant negative phase before and a predominant positive phase after 1994; thus, the analysis is performed for two subperiods: 1979–1994 (P1) and 1995–2014 (P2). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 62 publications
4
36
0
Order By: Relevance
“…The Tibetan Plateau (TP) has the highest elevation on Earth and presents a large snow cover area in cold seasons (Che et al, 2019; Chu et al, 2017; Pu et al, 2007; Wang et al, 2017; Wang, Wu, et al, 2019). Snow cover anomalies can significantly impact the surface energy budget and hydrological cycle as well as both local and remote climates (e.g., Blanford, 1884; Dey & Kumar, 1983; Ding et al, 2008, 2009; Hahn & Shukla, 1976; Jia et al, 2018; Lin & Wu, 2011, 2012; Liu et al, 2017; Mote & Kutney, 2012; Qian et al, 2019; Walker, 1910; Wang, Wu, et al, 2019; Wu & Kirtman, 2007; Zhao & Moore, 2004; Zwiers, 1993). The snow cover over the TP forms in autumn and can persist to the following winter and spring or even into summer in some high‐altitude regions (e.g., Li et al, 2017; Pu et al, 2007; Wang et al, 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Tibetan Plateau (TP) has the highest elevation on Earth and presents a large snow cover area in cold seasons (Che et al, 2019; Chu et al, 2017; Pu et al, 2007; Wang et al, 2017; Wang, Wu, et al, 2019). Snow cover anomalies can significantly impact the surface energy budget and hydrological cycle as well as both local and remote climates (e.g., Blanford, 1884; Dey & Kumar, 1983; Ding et al, 2008, 2009; Hahn & Shukla, 1976; Jia et al, 2018; Lin & Wu, 2011, 2012; Liu et al, 2017; Mote & Kutney, 2012; Qian et al, 2019; Walker, 1910; Wang, Wu, et al, 2019; Wu & Kirtman, 2007; Zhao & Moore, 2004; Zwiers, 1993). The snow cover over the TP forms in autumn and can persist to the following winter and spring or even into summer in some high‐altitude regions (e.g., Li et al, 2017; Pu et al, 2007; Wang et al, 2017, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As revealed by previous studies (Lin & Wu, 2011, 2012; Qian et al, 2019), autumn TP snow cover can affect the winter SAT over NA via the propagation of a snow‐related Rossby wave train. These previous studies suggest that TP snow cover can be an important climate predictor for NA winter SAT.…”
Section: Resultsmentioning
confidence: 67%
“…A longer training data set might be helpful for improving the forecasting skill of the XGBoost model. As an extension of previous work (Lin & Wu, 2011;Qian et al, 2019), the sensitivity of empirical model skill to the TP snow predictor is also investigated. It is shown that the additional use of the TP snow predictor can improve the forecast skill of the three empirical models but over different regions of NA.…”
Section: 1029/2020ea001140mentioning
confidence: 99%
See 1 more Smart Citation
“…The Tibetan Plateau snow cover (TPSC) and its variations exert substantial influences on the weather, climate and ecosystem of the Tibetan Plateau and its surrounding areas (You et al ., 2020). In most of the literature, TPSC is generally considered as an atmospheric indicator at interannual (e.g., Wu and Qian, 2003; Lin and Wu, 2011; Xiao and Duan, 2016; Wang et al ., 2017; Lyu et al ., 2018; Wang et al ., 2018; Qian et al ., 2019; Qiu et al ., 2019; Yuan et al ., 2019) and decadal time scales (e.g., Zhang et al ., 2004; Zhao and Moore, 2004; Wu et al ., 2012; Si and Ding, 2013); other studies have examined the long‐term trends of TPSC (e.g., Zhao and Moore, 2006; Zhao et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%